2018
DOI: 10.3892/ijo.2018.4646
|View full text |Cite
|
Sign up to set email alerts
|

miR‑381 and miR‑489 suppress cell proliferation and invasion by targeting CUL4B via the Wnt/β‑catenin pathway in gastric cancer

Abstract: Accumulating evidence has highlighted the critical role of cullin 4B (CUL4B) in driving tumourigenesis in several malignancies, including gastric cancer (GC); however, the mechanisms underlying CUL4B upregulation remain unclear. The dysregulation of microRNAs (miRNAs or miRs) is known to be involved in tumourigenesis. In this study, we report that the expression of miR-381 and miR-489 is downregulated and is negatively correlated with that of CUL4B in GC tissues and cell lines. Further analysis verified that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 43 publications
(47 reference statements)
1
24
0
Order By: Relevance
“…All analyses were presented as mean ± standard deviation calculated for three or more replicates. Statistical analyses were carried out using GraphPad prism 5 or the Statistical Package for Social Sciences, version 19.0 (SPSS, Chicago, IL), with P < .05 being considered statistically significant. Two-tailed the Student t test was used for statistical comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All analyses were presented as mean ± standard deviation calculated for three or more replicates. Statistical analyses were carried out using GraphPad prism 5 or the Statistical Package for Social Sciences, version 19.0 (SPSS, Chicago, IL), with P < .05 being considered statistically significant. Two-tailed the Student t test was used for statistical comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…CUL4B is a scaffold protein and might be involved in the nucleus‐based functions as it carries a nuclear localization signal in its N terminus and localizing in the nucleus . Previous studies have demonstrated that CUL4B is dysregulated in various malignancies and possesses potent oncogenic properties . CUL4B promotes histone and DNA methylation, recruits PRC2, leading to transcriptional silencing of tumor suppressor genes such as P16, PTEN, and Wnt antagonists, by catalyzing histone H2AK119 monoubiquitylation (H2AK119ub1) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study of gastric carcinoma, miR-23b-3p and miR-130a-5p appeared to affect cell growth, migration, and invasion by targeting CB1R via the Wnt/β-catenin signaling pathway [19]. Additionally, miR-381 and miR-489 have been found to decrease cell proliferation and invasion in gastric cancer by targeting CUL4B via the Wnt/β-catenin pathway [20].…”
Section: Microrna Dysregulation and Gastric Adenocarcinoma And Relatementioning
confidence: 99%
“…At present, a number of reports (5)(6)(7) have proven that microRNAs (miRNAS) are involved in the development of various tumors. miR-221 and miR-489 have been verified to have abnormal expression (8)(9)(10) in colorectal cancer and gastric cancer; however, miR-221 and miR-489 expression levels in breast cancer have been rarely reported. Therefore, in the present study it was speculated that miR-221 and miR-489 have also abnormal expression in breast cancer, and experimental analysis was carried out for verification.…”
Section: Introductionmentioning
confidence: 99%